Potentiometric Studies on Transition Metal Complexes of Substituted Derivative of Coumarin-Part 1 - K. B. Vyas; G. R. Jani; M. V. Hathi (E-Journal of Chemistry)
The formation constants of binary complexes of d10 metal ions Cu(II), Ni(II), Co(II) and Mn(II) with 3-[{3-(3’-chloro phenyl}-prop-2-enoyl]-4-hydroxy-6-methyl-2H-chromen-2-one have been studied by using Irving-Rossoti method at constant temperature 30±1 °C and ionic strength μ=0.1 M dM-3 was held constant using sodium nitrate as an electrolyte. The factors influencing formation and stabilities of binary complexes have been discussed.